PREDICTORS OF M-CONTINUANCE INTENTION: CASE OF USERS IN BOSNIA AND HERZEGOVINA - Amra Grcić; Ensar Mekić (Economic Review)
Even though researchers are increasingly studying various aspects of m-commerce, few of them focused on factors of m-continuance intention. The main aim of this study is to investigate if consumer innovativeness and social influence are statistically significant predictors of m-continuance intention. Based on the recent literature, first order structural equation model was proposed and tested. The empirical data was obtained from a questionnaire of 241 m-commerce users in Sarajevo Canton. Once the data was collected, factory data analysis was conducted to assure validity and reliability through items' loadings and Cronbach's Alpha values. Furthermore, the scales were tested for convergent validity through partial least-square path modelling using Smart PLS 3 software. For confirmatory factor analysis purpose, individual evaluation of items, variables as well as model fit was made. The results indicated that the effects of consumer innovativeness and social influence on m-continuance intention were significant and positive. It is recommended for future research to investigate the effects of other potential predictors of m-continuance intention with the focus on a larger sample and wider geographical region.